Analisis Jejak Karbon Dalam Proses Pembelajaran Kelas - Dirga, Agustinus; Setiawan, Temy; Breliastiti, Ririn (Owner : Riset dan Jurnal Akuntansi, 2024)
The environmental issue should have already become a primary concern and a crucial focal point for sustainability. One of the influencing factors is carbon dioxide (CO2) emissions, which have a significant impact on climate change. Electricity consumption contributes the largest share of carbon emissions in the energy sector, followed by transportation activities. This study aims to compare the levels of carbon emissions generated and the costs incurred in the face-to-face and online learning processes involving electricity consumption and transportation activities. The research employs a qualitative approach with a case study method. The population in this study consists of active accounting students at Bunda Mulia University, Serpong Campus, and no sampling is conducted to obtain the entire data, which includes primary data from observation and questionnaire. The tools used in this study are Microsoft Excel and jejakkarbonku.id for processing research samples. The results of the study indicate that electricity consumption is higher in face-to-face learning compared to online learning. Additionally, a greater level of carbon emissions is produced from face-to-face learning than online learning, with building electricity consumption surpassing transportation activities. The costs incurred for face-to-face learning are also higher than those for online learning. Despite face-to-face learning being the largest contributor to consumption, carbon emissions, and costs, it is perceived as more effective than online learning. Therefore, there is a need for solutions to address environmental issues while maintaining the effectiveness of education.